ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS FOR VBA EXCEL TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA DI MTS NURUL HIDAYAH BATUJAJAR - Pamungkas, Regi Ayu; Kulsum, Sri Islami; Chotimah, Siti (IKIP Siliwangi, 2020)
This study aims to determine the motivation to learn mathematics students after learning to use media for VBA Excel. The research was carried out in Mts Nurul Hidayah with the number of subjects being 25 students of grade 8A. The focus on what will be studied is the students' motivation to learn mathematics, with 50% positive statements and 50% negative statements presented which are adjusted to the indicators of mathematics learning motivation. Descriptive research with a qualitative approach used to achieve research objectives. 20 statements representing 6 indicators were given to students by given answer choices, namely strongly agree, agree, disagree, and disagree. Data analysis was carried out by giving points to each student's choice, then accumulating to get the final results and adjusting the categories including whether or not students' motivation to learn mathematics after learning using VBA for Excel. From the data tabulation results obtained an average of each indicator of learning motivation is 81.29%. In accordance with the large classification percent is in the very good category. So it can be said that students' motivation to learn mathematics is very good after learning to use media for VBA Excel.